From international experience to French case studies PORT-VERT: A French research project investigating various possibilities of bicycle-transit intermodality. - Soulas, Claude; Abours, Claude; Papon, Francis (My University, 2013)
The PORT-VERT research project investigated bicycle-transit intermodality. After a review of the state of the art and an analysis of German best practices, the project explored technical and organizational aspects, socio-economic analysis and behavioural surveys, architectural aspects, ergonomics (such as on-board loading), and the involvement of multiple players. Finally, case studies in and Rouen were considered. The main results found that to develop bicycle-transit intermodal use, the entire transport chain must be improved: the bicycle and its use, public transport (networks, stations, rolling stock) and intermodal facilities and services such as bicycle parking near stations. There is no single solution; individual contexts and the potential for increase in use must be considered. An application study was carried out in Marne-la-Vallée for a Parisian suburban train station serving a large university which showed how estimated potential use varies with different hypotheses and different local or global supporting measures.
Keywords: Verkehrsplanung; Stadtverkehr; Fahrradverkehr; Öffentlicher Verkehr; ÖPNV; Bike-and-Ride; Fahrradabstellanlage; Fallstudie